Disability due to maternal common mental disorders (CMDs) as a risk factor for chronic childhood malnutrition: cross-sectional study - Cavalcante-Neto, Jorge Lopes; Paula, Cristiane Silvestre de; Florêncio, Telma Maria de Menezes Toledo; Miranda, Claudio Torres de (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: The disability associated with maternal common mental disorders (CMDs) is among the possible explanations for the association between chronic childhood malnutrition and CMDs. CMDs may impair the mother’s ability to perform her role, particularly in deprived environments. The present study aimed to evaluate whether disability relating to CMDs could be part of the pathway of the association between childhood malnutrition and maternal CMDs. DESIGN AND SETTING: Cross-sectional study conducted in two institutions: one for malnourished children and another for eutrophic children living in a low-income community in the state of Alagoas, Brazil. METHOD: The cases consisted of 55 malnourished children aged from 12 to 60 months who were attending a nutritional rehabilitation center, with height-for-age z-scores < 2. The controls were 70 eutrophic children of the same age who were attending a day care center in the same area as the cases. The SelfReport Questionnaire made it possible to identify likely cases of maternal CMD. The Sheehan Disability Scale enabled evaluation of the associated disability. RESULTS: Chronic childhood malnutrition was significantly associated with maternal disability relating to CMDs (OR = 2.28; 95% CI: 1.02-5.1). The best logistic regression model using chronic childhood malnutrition as the dependent variable included the following independent variables: higher number of people living in the household; absence of the biological father from the household; and maternal disability relating to CMDs. CONCLUSIONS: If confirmed, the association between chronic childhood malnutrition and maternal disability relating to CMDs may be useful in helping to identify the causal chain between childhood malnutrition and maternal CMDs and to indicate environmental risk factors associated with chronic childhood malnutrition.